ENVIRONMENTAL FACTORS IN THE STRATEGIC PLANNING OF THE STEM SUBUNIT OF UNIVERSITY: REMARKS FOR A CASE STUDY - Norkus, Zenonas (Acta Paedagogica Vilnensia, 2011)
The article provides the outline for analysis of the economic, social, and political factors, shaping the field of activities of Lithuanian higher schools (universities). This outline was prepared while making the strengths, weaknesses, opportunities, threats analysis for the strategic plan of Vilnius university. The paper disputes several clichés about inefficiencies circulating in the Lithuanian mass media. Following theses are substantiated: (1) in purely economic terms, the Lithuanian higher education system is most efficient in Europe, because the cost of education at Lithuanian high schools are the least in comparison with other European countries. (2) Lithuanian higher school system is not inefficient in social terms, because even after graduating from the study programs of lower quality students acquire general human capital that is optimal under conditions of liberal market economy (in the sense of Peter Hall and David Soskice) taking shape in Lithuania, or prepare themselves for emigration career. (3) The most fatal mistake that was done while reforming the system of higher education in Lithunia, was the failure to credit Vilnius university with the status of national university. Because of this failure, there barely remains the chance that Lithuania will have not only folk universities, but also at least one research university.